1874 Cal. Stat. 465 - (:unkn) unknown (My University, 1874)
An Act For the Protection of the Property At East Park, in Sacramento County, ch. CCCXXI (311), § 1: Prohibited discharge of any gun, pistol, or firearm within the grounds of East park of Sacramento
Keywords: DISCHARGE